Analisis Pendapatan Usahatani Bawang Merah (Allium ascalonium L.) dan Tingkat Kesejahteraan Rumah Tangga Petani Bawang Merah di Kecamatan Belo Kabupaten Bima - Bakdiah Bakdiah; Danang Manumono; Ari Astuti (JURNAL ILMIAH AGRITAS, 2022)
This study aimed to determine the income of shallot farming, the contribution ofshallot farming income to family income, and the relationship between shallot farmingincome and the welfare level of shallot farmers. Respondents in this study amounted to 97shallot farmers from two villages, namely Ncera and Ngali villages. The samples weredtermined using simple random sampling, and the data analysi swas performed usingMicrosoft Excel and manual assistance. The average farming cost in MK with an area of5,799 m2 is Rp. 51,121,645, the average revenue is Rp. 176,143,944, and an average incomeof Rp. 125,022,299 The cost of farming in MH with an area of 5,799 m2 is Rp. 51,165,356,the average receipt of Rp. 163,079,280, and an average income of Rp. 111,913,924. Thecontribution of shallot farming income to household income is moderate, which is at 57.5%.The welfare level of shallot farmers is classified as a prosperous household with apercentage of 90% or 87 farmers. The relationship between income and the level of welfareof shallot farmers is negative and very weak; it is because the wealth of prosperous farmersare not due to the income of shallot farming from another income besides shallot farming.Farmers have jobs that generate income outside of shallot farming to cover expenses so thatthey are prosperous. One of the incomes comes from cattle, amounting to Rp. 54,071,429in 2021 and outside agriculture, the highest is income from entrepreneurship, which is Rp.65,051,429 in 2021. Farmers in Belo sub-district are expected to improve their skills andknowledge in shallot farming.